The largest trade agreement in the world - Vallejo Zamudio, Luis Eudoro (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The Trans-Pacific Partnership (TPP) is an agreement that was established in the early days of October, after eight years of negotiations, which the United States, Canada, Japan, Australia, Mexico, Chile, Peru, Malaysia, New Zealand, Singapore, Vietnam and Brunei are a part of. The economies that have signed the agreement show unequal levels of development and have different production sectors and interests, and, yet despite this, over the last few years, they have sought the broadest consensus possible in order to create a business alliance that will allow them to trade with low tariffs.